Potential Anti-Bacterial Extract of Red Belt (Piper Crocatum Ruiz & Pav.) Against Staphylococcus Epidermidis - Nanda Dhea Ayu Sawitri; Iin Novita Nurhidayati Mahmuda (Rifa'Institute, 2022)
Introduction: Red betel leaf is a plant native to Indonesia which is used as an antiseptic, anti-cancer, and infection treatment. The ethanol content of red betel leaf extract is known to have antibacterial activity. Among them there are alkaloids, flavonoids, essential oils, tannins, and saponins. Objective: to determine the potential of red betel leaf extract (Piper crocatum Ruiz & Pav.) in inhibiting the growth of Staphylococcus epidermidis bacteria. Methods: Staphylococcus epidermidis bacteria were divided into 5 groups, PEG 5% as negative control, clindamycin 30µg/disk as positive control, extract 20%, 40%, 80% as treatment group. Measuring the zone of inhibition using a ruler. Result and Discussion: Staphylococcus epidermidis inhibition zone was formed at concentrations of 20%, 40%, 80%. Kruskal Wallis analysis showed significant results of p = 0.000 for bacteria. Conclusion: Red betel leaf extract (Piper crocatum Ruiz & Pav.) has significant antibacterial activity against Staphylococcus epidermidis. The higher the concentration, the larger the diameter of the inhibition zone.